2007
DOI: 10.1016/j.jcrysgro.2007.02.035
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation and growth of calcium phosphate by amelogenin

Abstract: The nucleation processes involved in calcium phosphate formation in tooth enamel are not well understood but are believed to involve proteins in the extracellular matrix. The ability of one enamel protein, amelogenin, to promote the nucleation and growth of calcium phosphate was studied in an in vitro system involving metastable supersaturated solutions. It was found that recombinant amelogenin (rM179 and rp(H)M180) promoted the nucleation of calcium phosphate compared to solutions without protein. The amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 47 publications
8
74
2
1
Order By: Relevance
“…This critical value can be expressed as a function of the specific interfacial energy, volume of the growth units, supersaturation, and temperature (22). Although it is not known whether this relation can be simply applied to complex biomineralization systems, it has been proposed that biomolecules interact with the surfaces of embryonic crystals to reduce interfacial energy, resulting in smaller critical radius (6,12,(23)(24)(25). As shown in earlier works (13,17) and in the present study, compounds of calcium phosphate can exist as large (submicrometer sizes) amorphous particles for a period before being supplanted by large depositions of crystalline calcium phosphate.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This critical value can be expressed as a function of the specific interfacial energy, volume of the growth units, supersaturation, and temperature (22). Although it is not known whether this relation can be simply applied to complex biomineralization systems, it has been proposed that biomolecules interact with the surfaces of embryonic crystals to reduce interfacial energy, resulting in smaller critical radius (6,12,(23)(24)(25). As shown in earlier works (13,17) and in the present study, compounds of calcium phosphate can exist as large (submicrometer sizes) amorphous particles for a period before being supplanted by large depositions of crystalline calcium phosphate.…”
Section: Resultssupporting
confidence: 54%
“…He et al (6) have shown that two peptide motifs identified in DMP1 [motif-A (ESQES) and motif-B (QESQSEQDS)] enhanced in vitro HAP formation when immobilized on a glass plate (6). Along with DMP1's motifs, several peptides and proteins have been shown to act as accelerators of HAP formation, and it has been suggested that these molecules mediate nucleation during crystal formation (12)(13)(14). The purpose of our experiment was to gain insight into the molecular mechanism by which the peptide motifs of DMP1 facilitate HAP formation through our synthetic approach (15).…”
mentioning
confidence: 99%
“…These studies were carried out in modestly supersaturated solutions that undergo spontaneous formation of HA in ϳ700 h under near-physiological pH, temperature, and ionic strength conditions. However, at somewhat higher concentrations (65 g/ml) the induction time was found to increase (relative to that observed at 6.5 g/ml), and lesser amounts of HA precipitated (41). It has also been reported (43) that higher concentrations (1.6 mg/ml) of recombinant full-length human amelogenin (rH174) accelerated the growth of a mineral layer (based on AFM height measurements) on fluoroapatite crystals, relative to controls, under driving forces for mineralization that were lower than those used in the present study.…”
Section: Discussionmentioning
confidence: 63%
“…In developing enamel matrix, the majority of the organic extracellular matrix proteins are comprised by a group of highly conserved, structural proteins called amelogenins [2]. Amelogenins have been identified to function as cell adhesion molecules and to facilitate nucleation and growth of hydroxyapatite crystals during the mineralization phase of amelogenesis [3]. As a result of amelogenin mRNA alternative splicing, different amelogenin isoforms are detected in the developing enamel matrix [4].…”
Section: Introductionmentioning
confidence: 99%